"Urban Farming Is Going High Tech": Digital Urban Agriculture's Links to Gentrification and Land Use. Issue 1 (2nd January 2020) - Carolan, Michael
Abstract: Problem, research strategy, and findings: How do traditional forms of urban agriculture and the newer digital urban agriculture converge and diverge from one another in terms of land use and gentrification? I interrogate the subject of digital urban agriculture with data from 82 semistructured interviews and notes taken during public forms and tours of facilities. Respondents were located in Denver (CO; n  = 30), New York (NY; n  = 26), and San Francisco (CA; n  = 26) and held positions ranging from community organizers, investors, local food powerbrokers, and planners to engineers involved in facilitating urban foodways based on vertical farming, automation, and related technologies. I find digital platforms—systems exhibiting characteristics including real-time surveillance, artificial intelligence, and automation—share similarities with traditional urban farming systems. Both platforms have the potential to disrupt dominant political economies and also have links to gentrification and other inequitable land use patterns. Potential divergences include differences in a) social, cultural, economic, human, and built capital barriers and outcomes; b) land use life course; and c) zoning. Takeaway for practice: Digital urban farming systems inhabit a regulatory gray area; respondents encountered agricultural, industrial, or commercial zoning permits. The "digital" aspects of these systems contributed to this ambiguity and are used by powerbrokers to obtain further zoning permission than is possible with traditional urban agriculture. Compared with more traditional urban farming systems, digital urban agriculture taps into different forms of human capital. Finally, my findings are inconclusive on the issue of land use life course. Some data indicate digital farms will remain in urban cores, whereas other evidence points to the eventual migration of these platforms to the metropolitan periphery.